Viral spot exants in children - R. A. Ravodin; V. B. Rovnyi; Yu. S. Ermolaeva (Журнал инфектологии)
The article analyzes the clinical manifestations of the most common viral infectious diseases in children, accompanied by spotty exanthema, provides brief data on the etiology, pathogenesis and epidemiology of these infections, shows photographs for each of the described nosological forms from the authors' personal archives.